2021
DOI: 10.1021/acs.nanolett.0c04244
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Fault Driven Phase Transformation in CrCoNi Medium Entropy Alloy

Abstract: Phase transformation is an effective means to increase the ductility of a material. However, even for a commonly observed face-centered-cubic to hexagonal-close-packed (fcc-tohcp) phase transformation, the underlying mechanisms are far from being settled. In fact, different transformation pathways have been proposed, especially with regard to nucleation of the hcp phase at the nanoscale. In CrCoNi, a so-called medium-entropy alloy, an fccto-hcp phase transformation has long been anticipated. Here, we report an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Intriguingly, 0 K ab initio calculations suggest that, for a given degree of (dis)order, hcp CrCoNi has a lower Gibbs energy than the fcc equivalent; this relationship inverts at higher temperatures owing to the activation of phonon modes ( 41 ) and likely spin fluctuations as well ( 42 ). This picture is consistent with the observation of somewhat larger hcp lamellae at 20 K, but it must be asked why, in contrast to similarly metastable Co ( 43 ) or CoNi alloys ( 44 ), low-temperature deformation still only minimally induces the martensitic hcp phase, which has been reported in quantities ranging from 0 to a maximum of a few vol % ( 18 , 25 , 45 ). This observation is also consistent with our in situ neutron diffraction data (fig.…”
Section: Discussionsupporting
confidence: 83%
“…Intriguingly, 0 K ab initio calculations suggest that, for a given degree of (dis)order, hcp CrCoNi has a lower Gibbs energy than the fcc equivalent; this relationship inverts at higher temperatures owing to the activation of phonon modes ( 41 ) and likely spin fluctuations as well ( 42 ). This picture is consistent with the observation of somewhat larger hcp lamellae at 20 K, but it must be asked why, in contrast to similarly metastable Co ( 43 ) or CoNi alloys ( 44 ), low-temperature deformation still only minimally induces the martensitic hcp phase, which has been reported in quantities ranging from 0 to a maximum of a few vol % ( 18 , 25 , 45 ). This observation is also consistent with our in situ neutron diffraction data (fig.…”
Section: Discussionsupporting
confidence: 83%
“…For example, equiatomic CrMnFeCoNi HEA and CoCrNi MEA possess exceptional combinations of tensile strength and ductility (tensile strength of ~1 GPa as well as ductility exceeding 60%) at 77 K, and ultra-high fracture toughness at both room temperature and 77 K (K J1C > 200 MPa√m), making them one class of the toughest metallic materials reported so far [17,23,26]. Such exceptional mechanical properties are attributed to continuous steady strain-hardening, resulting from extensive dislocation activities and deformation-induced nanotwinning [18,21,22,27]. These fcc-structured HEAs can be used as ideal alloy bases to design high-strength and high-ductility structural materials through further compositional and microstructural engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that metastable high-entropy dual-phase alloys can overcome the strength-ductility trade-off by interface hardening and transformation-induced hardening, realized by reducing the stacking fault energy (SFE) via tailoring chemical composition [15,19,24,[28][29][30][31][32][33]. The tensile strength and ductility are simultaneously enhanced due to heterogeneous microstructures, such as gradient nanotwins, gradient nano-grains, or recrystallized and non-recrystallized grains arranged in hierarchical structures with characteristic dimensions spanning from submicron scale to micro-scale, that are obtained by coldrolling and annealing [9,16,27,34,35]. Note that single-phase fcc CrFeCoNi-based HEAs often have a very low SFE, which promotes deformation-induced nanotwinning and martensitic phase transformation [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the intrinsic material properties, another parameter that would control deformation microstructure of grain is its crystallographic orientation because it determines the forms of active slip system, e.g., single-planar, double-planar, and multipleplanar slip (15). While planar slip bands, deformation nanotwins, and deformation hexagonal close-packed (hcp) structures are widely observed in experiments (16)(17)(18), understanding the underpinning dislocation mechanism and their relationship with the grain orientation remains a challenging problem because of the inability of in-situ tracking dislocations in three-dimensional bulk materials during straining. Leveraging on large-scale deformation simulations of a model fcc CrCoNi alloy at the atomistic level, this study notably different characteristics of dislocation patterning and deformation microstructure evolution, substantially depending on grain orientation.…”
Section: Introductionmentioning
confidence: 99%